Poder saber e prazer: os afetos políticos mobilizados no consumo feminino de pornografia - Veiga, Maria Júlia Alencastro (2020)
We live in a context of extensive media production and consumption in which images play a central role. Preciado (2018), in effect, defines contemporaneity as the pharmacopornographic era. From this context, we conducted 13 qualitative in-depth interviews with women that consume pornography and analyzed, in this dissertation, the political affections mobilized by it. We understand that the pornographic image has a great synesthetic and political character, acting as a way of Foucauldian Power Knowledge, building pleasures and gender policies. Therefore, we present, in this work, a study of the reception of pornography, from a little explored place, the feminine. In summary, we problematize the possibilities of affective engagement generated by the synesthetic character of the pornographic image in consumer culture from the eyes and voice of consumers and we discuss the possibility that this consumption is seen as political